Social Competence of Islamic Religious Education Teachers in Improving Students' Characteristics Class Xi of SMK Ibnu Sina Batam - Sumianti; Afi Parnawi; Abdullah (PT Inovasi Pratama Internasional, 2023)
Teacher competence is an important thing that must be possessed by a teacher as an educator in shaping the personality and morals of students as students. The purpose of this study was to find out how the competence of PAI teachers can shape the morale and personality of class XI students at SMK Ibnu Sina Batam and the factors that hinder PAI teachers in improving character. This research method uses a qualitative approach that seeks to describe the Social Competence of Islamic Religious Education Teachers in Improving the Characteristics of SMK Ibnu Sina Students in Batam City. The supporting factors for teacher social competence are the school principal's program to improve the social competence of Islamic religious education teachers, namely sending teachers to attend seminars and training from DikNas and outside the DikNas. Participate in teacher work strengthening training (PKG), educational institutions that support the development and learning of the Islamic religion in particular, infrastructure, Islamic religious education teachers are graduates of Islamic religious education. As for the Inhibiting Factors. Internal, namely coming from the teacher himself such as a lack of communication with colleagues in the profession and a lack of communication with parents of students and the community around the environment of the Ibn Sina educational foundation. Externally comes from students, students' family environment, lack of attention from parents to children's behavior because people are preoccupied with working and earning a living. Community environment, lack of parental supervision of the association of their children. So that parents do not know their children associate with anyone. So there needs to be a synergy between teachers and parents.